Crystal structure of atazanavir, C38H52N6O7. Issue 2 (June 2020) - Kaduk, James A.; Gindhart, Amy M.; Blanton, Thomas N.
Abstract : The crystal structure of atazanavir has been solved and refined using synchrotron X-ray powder diffraction data and optimized using density functional techniques. Atazanavir crystallizes in space group P 21 (#4) with a = 15.33545(7), b = 5.90396(3), c = 21.56949(13) Å, β = 96.2923(4)°, V = 1941.134(11) Å 3, and Z = 2. Despite being labeled as "atazanavir sulfate", the commercial reagent sample consisted of atazanavir free base. The structure consists of an array of extended-conformation molecules parallel to the ac -plane. Although the atazanavir molecule contains only four classical hydrogen bond donors, hydrogen bonding is, surprisingly, important to the crystal energy. Both intra- and intermolecular hydrogen bonds are significant. The hydroxyl group forms bifurcated intramolecular hydrogen bonds to a carbonyl oxygen atom and an amide nitrogen. Several amide nitrogens act as donors to the hydroxyl group and carbonyl oxygen atoms. An amide nitrogen acts as a donor to another amide nitrogen. Several methyl, methylene, methyne, and phenyl hydrogens participate in hydrogen bonds to carbonyl oxygens, an amide nitrogen, and the pyridine nitrogen. The powder pattern is included in the Powder Diffraction File™ as entry 00-065-1426.